Combined Tissue Transfer for Extensive Lower Limb Complex Defects: Flow-through Flaps, Chimera, and “Orochi” Flaps - Koshima, Isao (Journal of Reconstructive Microsurgery, 2020)
Perforator flaps can be raised anywhere in the body, with minimal donor-site deformity, and can be made into custom-made combined composite flaps, especially for severe complex defects such as osteomyelitis of the lower limbs. Here, we report on the representative application of the combined tissue transfers for complex leg defects. For a wide range of complex defects in the lower extremity, it is necessary to perform reliable revascularization by bypass or flow-through type or vein graft. At the same time, a chimeric or “Orochi” type combined transfer using a minimally invasive perforator flaps and a well-vascularized bone flap are useful. In the case of nerve palsy, it could be possible to combine vascularized nerve flaps. Combined tissue transfers with less invasive donor will be more available in the future.
Keywords: combined tissue transfer; Orochi flap; complex defect; chimera flap; flow-through flap